2017
DOI: 10.1124/jpet.117.243865
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Rostral Ventrolateral Medulla Cystathionine-γ Lyase Activity Underlies Moxonidine-Evoked Neuroprotection and Sympathoinhibition in Diabetic Rats

Abstract: We recently demonstrated a fundamental role for cystathionine- lyase (CSE)-derived hydrogen sulfide (HS) in the cardioprotective effect of the centrally acting drug moxonidine in diabetic rats. Whether a downregulated CSE/HS system in the rostral ventrolateral medulla (RVLM) underlies neuronal oxidative stress and sympathoexcitation in diabetes has not been investigated. Along with addressing this question, we tested the hypothesis that moxonidine prevents the diabetes-evoked neurochemical effects by restoring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…As a foundation to our study, we showed that incubating CHO cells in elevated glucose caused a concentration‐dependent oxidative stress and cell death (Figure 1), which agrees with previous reports (Fouda & Abdel‐Rahman, 2017; Fouda et al, 2018; Lamers, Almeida, Vicente‐Manzanares, Horwitz, & Santos, 2011). High glucose‐induced increase in ROS production is correlated to apoptosis and cell death (Fouda & Abdel‐Rahman, 2017; Fouda et al, 2018) due to impairment of pro‐survival signalling pathways such as Akt (Van Linthout et al, 2008) and activation of pro‐inflammatory and cell death pathways such as NF‐κB (Mariappan et al, 2010). In addition, our current findings implicate the role of Na v 1.5 as a downstream target for oxidative stress in cytotoxicity provoked by high glucose (Figure 1).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As a foundation to our study, we showed that incubating CHO cells in elevated glucose caused a concentration‐dependent oxidative stress and cell death (Figure 1), which agrees with previous reports (Fouda & Abdel‐Rahman, 2017; Fouda et al, 2018; Lamers, Almeida, Vicente‐Manzanares, Horwitz, & Santos, 2011). High glucose‐induced increase in ROS production is correlated to apoptosis and cell death (Fouda & Abdel‐Rahman, 2017; Fouda et al, 2018) due to impairment of pro‐survival signalling pathways such as Akt (Van Linthout et al, 2008) and activation of pro‐inflammatory and cell death pathways such as NF‐κB (Mariappan et al, 2010). In addition, our current findings implicate the role of Na v 1.5 as a downstream target for oxidative stress in cytotoxicity provoked by high glucose (Figure 1).…”
Section: Discussionsupporting
confidence: 92%
“…Fluorescence intensity was measured 30 min after the reaction initiation using a microplate fluorescence reader set at excitation (485 nm)/emission (530 nm) according to the manufacturer's instructions (Abcam, ab113851). The ROS level was determined as relative fluorescence units of generated DCF using standard curve of DCF (Fouda & Abdel‐Rahman, 2017; Fouda, El‐Sayed, & Abdel‐Rahman, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…31 MOX has also been demonstrated to alleviate RVLM oxidative stress and neuronal injury in diabetic rats. 32 In conclusion, the obtained results show no negative interactions between MOX and AEDs as concerns their anticonvulsant effects in MES test. These drug combinations were also free from adverse effects investigated in behavioural tests.…”
Section: Discussionmentioning
confidence: 55%
“…Injection of the GABA A receptor antagonist bicuculline into the commissural nucleus of the solitary tract reduced hypotension and sympathoinhibition induced by MOX 31 . MOX has also been demonstrated to alleviate RVLM oxidative stress and neuronal injury in diabetic rats 32 …”
Section: Discussionmentioning
confidence: 95%
“…By the same token, inflammation could lead to increase in oxidative stress production (Kobayashi et al., 2003). In addition, oxidative stress is correlated with apoptosis and cell death in both in vivo and in vitro studies (Fouda & Abdel‐Rahman, 2017; Fouda et al., 2018; Fouda, Leffler et al., 2020) due to impairment of pro‐survival signalling pathways such as Akt (Van Linthout et al., 2008) and activation of pro‐inflammatory and cell death pathways such as NF‐κB (Mariappan et al., 2010). Moreover, oxidative stress affects the biophysical properties of Na v through lipoxidation of the cell membrane and/or the inhibition of Na v trafficking to the cell membrane (Liu et al., 2013; Nakajima et al., 2010).…”
Section: Introductionmentioning
confidence: 99%